Pereira problem solving: Business research methodology to explore open innovation - Leandro Pereira; Ricardo Santos; Mariana Sempiterno; Renato J. Lopes da Costa; Álvaro Lopes Dias; Nelson J. dos Santos António (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Problem solving skills are increasingly important to be able to tackle the complex problems encountered in the business world. Nowadays is increasingly important to achieve sustainable development, focusing not only on economic profit but also on creating social value. It is widely agreed that the principles of scientific management can lead to more effective solutions for complex problems. Problems have to be looked at objectively, with methodology and intellectual integrity and modesty. Several techniques have been developed to help analyze the causes of the problem or formulate solutions. Although these business research techniques are important tools, they are presented as isolated measures. Pereira Problem Solving methodology presented provides guide to address business and management problems. It is an integrative and easy-to-use instrument that helps organizations adopt scientific management practices and will enhance the efficiency of the solutions encountered.
Keywords: 650; business research techniques; problem formulation; problem solving; scientific management; solution formulation